Possible involvement of microglial P2RY12 and peripheral IL-10 in postpartum depression - Kim, Hui-Ju; You, Min-Jung; Sung, Soyoung; Rim, Chan; Kwon, Min-Soo (Frontiers in Cellular Neuroscience, 2023)
Postpartum depression (PPD) is another type of depression including emotional fluctuation, fatigue, and anxiety. Based on the specific event like a giving birth, it can be speculated that PPD might have its specific mechanism. Here, we confirmed that dexamethasone (DEX) admiminstration during pregnancy (gestation day 16-18) induced depressive-and anxiety-like behaviors in dam (DEX-dam) after weaing period (3 weeks). DEX-dam showed anxiety-like behaviors in open fied test (OFT) and light-dark test (LD). In addition, DEX-dam exhibited depressive-like behaviors with the increased immobility time in forced swimming test (TST). Molecular analysis confirmed that microglia, rather than neuron, astrocytes, and oligodendrocytes, are invovled in anxiey/depressive-like behaviors. Notably, p2ry12, homeostatic gene and purinoceptor, along with hyper-ramified form, was reduced in the hippocampus of DEX-dam. In addition, we found that IL-10 mRNA was reduced in lymph node without alteration of pro-inflammatory cytokines such as TNF-, IL-1, and IL-6. Interestingly, anxiety/depressive-like behaviors of DEX-dam were restored with the normalization of p2ry12 and IL-10 after 10 weeks postpartum without anti-depressants. Our results propose that stress hormone elevation during pregancy might be associated with PPD via microglial P2RY12 and peripheral IL-10.